Designing Online Grocery Stores to Support Healthy Eating for Weight Loss. (29th May 2020) - Harnack, Lisa; French, Simone; Redden, Joseph; Sherwood, Nancy; Rivera, Gabrielle; Valluri, Sruthi; Tahir, Muna
Abstract: Objectives: To begin development of online grocery store design features that could support healthful food purchasing by shoppers who are trying to lose weight, using a Value Proposition Design approach to product development. Methods: One-on-one interviews were conducted with adults who reported they were trying to lose weight (n = 25) to gain insight into their shopping needs and perceptions. Interview results were used to identify four potential online grocery shopping features that could support healthful food purchase decisions. Prototypes were developed for each feature, and one-on-one interviews were conducted with a different sample of adults who reported trying to lose weight (n = 25) to gather feedback on the prototypes. Results: Based on customer needs identified through insight interview, the following four potential online grocery store features were devised and prototyped by the research team: 1) Nutritional quality rating of shopping cart items purchased, with suggestions for improvement provided; 2) Menu planning support tool to provide menu and recipe suggestions tailored to individual preferences; 3) An interactive virtual grocery aisle designed as a fun way to discover healthy products and meal ideas; and 4) A healthy shopping preference option to opt into a shopping experience that prioritizes the display and advertising of foods that align with the shopper's health and nutrition goals. Results from feedback interviews indicated that the menu planning support tool and the healthy shopping preference option were both highly positively rated and believed to be effective in helping support healthy food choices by most participants. Conclusions: Further development and evaluation work is warranted for the online grocery store features found to be most highly rated. This study illustrates application of a design thinking approach to developing nutrition promotion related products/programs. Funding Sources: University of Minnesota JB Hawley Faculty Research Award.